Efektivitas Daun Kemangi (Ocimum Sanctum L.) dalam Menurunkan Halitosis yang Berhubungan dengan Indeks DMF-T dan OHI-S - Enny Willianti (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
Halitosis is a term that describes an unpleasant odor from the breath. The unpleasant odor is caused by the decaying activity of gram-negative microorganisms. The causes of halitosis are usually due to poor oral hygiene, deep caries, periodontal disease, oral infection, dry mouth, smoking, mucosal ulceration, pericoronitis, food residue in the mouth, and tongue coating. The essential oil in basil leaves is widely reported to have antibacterial activity, both gram-positive and gram-negative bacteria, fungi, and molds. The purpose of this study was to determine the effectiveness of basil leaves (Ocimum sanctum L.) in reducing halitosis associated with DMF-T index and OHI-S. This quantitative research design is a quasi-experimental, which is giving treatment to the sample group. The number of samples is 30 people. The technique used in this research is quota sampling method. The tool used to determine the halitosis score is a halimeter. The data obtained in the form of halitosis scores before and after using basil leaves were tested using the Wilcoxon non-parametric test. After that, to find out the relationship between DMF-T and OHI-S indexes, it was tested using a correlation test. Data analysis using Wilcoxon, it showed that basil leaves were effective in reducing halitosis scores, because the value of sig.(2-tailed) α<0.05. With the correlation test, the results obtained p <0.01, then there is a significant relationship between halitosis and DMF-T. And there is a significant relationship between halitosis and OHI-S because the p value < 0.01. The results of the study was shown that basil was effective in reducing halitosis. There is a relationship between halitosis with DMF-T and OHI-S indices.